Delta-Like Protein 3 Expression in Paired Chemonaive and Chemorelapsed Small Cell Lung Cancer Samples - Kuempers, Christiane; Jagomast, Tobias; Krupar, Rosemarie; Paulsen, Finn-Ole; Heidel, Carsten; Ribbat-Idel, Julika; Idel, Christian; Märkl, Bruno; Anlauf, Martin; Berezowska, Sabina; Tiemann, Markus; Bösmüller, Hans; et al. (Frontiers in Medicine, 2021)
Rovalpituzumab tesirine (Rova-T), an antibody-drug conjugate directed against Delta-like protein 3 (DLL3), is under development for patients with SCLC. Since SCLC is rarely biopsied in the course of disease, data regarding DLL3 expression in relapses is not available. The aim of this study was to investigate the expression of DLL3 in chemorelapsed (but untreated with Rova-T) SCLC samples and compare the results with chemonaive counterparts. Two evaluation methods to assess DLL3 expression were explored. Additionally, we assessed if DLL3 expression of chemorelapsed and/or chemonaive samples has prognostic impact and if it correlates with other clinicopathological data. The study included 30 paired SCLC samples which were stained with an anti DLL3 antibody. DLL3 expression was assessed using tumor proportion score (TPS) and H-Score and was categorized as DLL3 low (TPS <50%, H-Score ≤150) and DLL3 high (TPS ≥ 50%, H-score >150). Expression data were correlated with clinicopathological characteristics. Kaplan-Meier curves were used to illustrate overall survival (OS) depending on DLL3 expression in chemonaive and chemorelapsed samples, respectively, and depending on dynamics of expression during course of therapy. DLL3 was expressed in 86.6% chemonaive and 80% chemorelapsed SCLC samples, without significant difference between the two groups. However, extend of expression varied in a substantial proportion of pairs (36.6% with TPS, 43.3% with H-Score), defined as a shift from low to high or high to low expression.TPS and H-Score provided comparable results. There were no profound correlations with clinico-pathological data. Survival analysis revealed a trend towards a more favorable OS in DLL low expressing chemonaive SCLC (p=0.57) and in turn in DLL3 high expressing chemorelapsed SCLC (p=0.42), as well as in SCLC demonstrating a shift from low to high expression (p=0.56) without being statistically significant. This is the first study to investigate DLL3 expression in a large cohort of rare paired chemonaive-chemorelapsed SCLC specimens. Comparative analysis revealed that DLL3 expression was not stable during course of therapy, suggesting therapy-based alterations. Unlike in chemonaive samples, a high DLL3 expression in chemorelapsed samples indicated a trend for a more favorable prognosis. Our results highlight the importance to investigate DLL3 in latest chemorelapsed SCLC tumor tissue.